Performance Of Combustion Chamber For Micro Gas Turbine (MGT) Application Running On Palm Oil - Chan, Jian Siang (Universiti Sains Malaysia, 2022)
Malaysia is a country that rich in biomass which leads a high global requirement for utilizing renewable energy resources in gas turbines to ensure a sustainable green environment. Combined heat and power (CHP) generation units based on Micro Gas Turbines (MGT) are versatile and reliable for on-site applications and they are designed to have a small and compact structure which allows them more vulnerable to internal leakages compared to other heavy-duty gas turbines. In this paper, a start-up test on performance of combustion chamber of single stage micro gas turbine application running on palm oil has carried out. A modification on design of a combustion chamber for micro-gas turbine was performed by using Computer-Aided Design (CAD) software, SOLIDWORKS then optimized by computational fluid dynamics (CFD) simulation software, ANSYS-FLUENT program followed by start-up test on MGT setup and trial process. Fuel that has used in MGT is vegetable oil which classified as low-grade renewable biofuel. Moreover, a start-up test on combustion characterization for the single stage MGT was carried out. Observations on performance of single stage MGT during start-up trials operation are obtained which include performance of biofuel evaporation and atomization, performance of flame and performance of turbine. Besides, simulation results were performed and developed based on several parameters such as total temperature, mole fraction of CO, mole fraction of pollutant NOx, and acoustics power level. For acoustic power level, eight different position planes were set along the combustion chamber. The results showed that the highest acoustic power level is 100.153 dB at position x=0.1m while lowest acoustic power level is 40.5497 dB at position x=0.4m. The microphones are recommended to be placed at position x=0.1m to solve the reverberation issues. Several recommendations of future work were given to utilise and improve the performance of combustion chamber for single stage MGT application.